Complexos fosfínicos/diimínicos de rutênio II: ensaios na captura e transformação catalítica do CO2 - Santos, Lucas da Silva dos (2023)
This work describes the synthesis and characterization of three new mononuclear ruthenium II complexes containing symmetric diimine ligands and monophosphines. The complexes were obtained by replacing a PPh3 (triphenylphosphine) by a diimine ligand, in the coordination sphere of the precursor complex [RuCl2(PPh3)3], in an argon atmosphere, using toluene as solvent. The diimine ligands used in the synthesis of these complexes have methyl groups in the ortho and / or para positions of the aromatic rings and were synthesized from condensation reactions of anilines and glyoxal (dialdehyde with formula C2H2O2) in the presence of water and isopropanol as solvent. The results of electronic absorption spectroscopy in the UV/Vis region, aided in the DT-DFT calculations, and the analysis by vibrational spectroscopy in the IR region suggest the coordination of the diimine ligand to the precursor complex. Electrochemical analyzes by cyclic voltammetry for the complexes showed oxidation and reduction potential values consistent with their structures. The 1H NMR spectra for the diiminic ligands showed signals close to 8.44 and 8.11 ppm, which refer to the hydrogen nucleus linked to the iminic carbons. The 13C NMR spectra for the diiminic ligands showed signals close to 163.50 and 159.00 ppm, which refer to the carbon nucleus of the iminic groups, directly linked to the nitrogen atoms. The 31P{1H} NMR spectra for the complexes [RuCl2(PPh3)2(2,4,6- Trime)] and [RuCl2(PPh3)2(2,6-Dime)] showed only one singlet, suggesting the formation of a single cis isomer, with nomenclature directed to chlorines. The 31P{1H} NMR for the complex [RuCl2(PPh3)2(2,4-Dime)], showed the presence of a cis-trans mixture, with three possible stereoisomers. Conductometric analyzes determined that the complexes do not behave as electrolytes in solution, which is consistent with their monomeric structures of the [RuCl2(PPh3)2(N-N)] type. The catalytic tests of hydrogenation and hydrogen transfer from isopropanol in the reduction of CO2 showed that the complexes do not show activity. During the catalytic assays, a secondary reaction was observed where KOH captures the CO2 dissolved in the isopropanol solution, which resulted in the direct precipitation of pure potassium bicarbonate. With this, the reaction conditions proposed here can be used as a form of technology for the capture, utilization and storage of CO2.